THE KINSHIP TERMS OF TRADITIONAL AND MODERN SOCIETIES IN EAST LOMBOK, WEST NUSA TENGGARA - RAHMATULLAH, RATIH (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: componential analysis, kinship, Sasak language, traditional society,modern society, East Lombok.Kinship is relations shared by human through blood tie and marriage. Kinship terms are used to express the relations. In this study, the writer identified kinship terms used by traditional and modern society of Sasak in East Lombok. There are two problems of the study, they are: (1) What Sasak kinship terms are used by traditional society in Limbungan and modern society in Selong district; (2) What differences are found in Sasak kinship terms between Limbungan villagers and Sasak modern society of Selong district based on the lexical and the componential analysis of the terms.The study used qualitative approach, employing in total 40 participants. 10 participants were Limbungan villagers and 30 participants were Selong citizens. 30 participants from Selong were divided into 3 groups, namely students group, modern job group, and social and politic organizations group. The numbers of participants were not same considering the difference of total population in both societies. All participants were required to answer the questionnaires. To analyse the data, the writer employed componential analysis approach by Kreidler (1998) to trace the meaning of each kinship term.This study reveals that Sasak kinship terms like Amaq, Inaq, and Amaq Kaka are still used in traditional society though there are also some adapted kinship terms from Bahasa Indonesia like Kakak, Adiq, and Ipar. Meanwhile in modern society, other languages like Javanese and Bahasa Indonesia kinship terms are also used by the citizens. It can be seen from the kinship terms Mamak, Bapak, Pak De and Bu De which are used by modern society. Lexical differences can be found in the terms for addressing parents’ younger siblings, and nephew or niece. In terms of componential analysis [male] and [female] semantic features are identified more in modern society since they tend to determine the sex the person they refer to.For the next researchers, similar study can be conducted using descriptive qualitative approach. Through descriptive qualitative approach, the next researcher may know the percentage of people who still apply Sasak kinship terms and at the same time can describe the phenomenon holistically. Kinship studies in other vernaculars employing other theories are also welcomed.